Use of Wavelet Analysis for Determining the Stability of the Banking System - Jur'evna Fedorova, Irina; Bogdanovich Rubinov, Renold; Valentinovich Berdysev, Alexander; Ivanovna Ryabchenko, Lyudmila; Sergeevich Matveevskii, Sergey (International Journal of Engineering and Technology, 2018)
The possibility and feasibility of using wavelet analysis to disclose the stability of the banking system operation were justified in the article. The main stages of wavelet analysis for disclosing the stability of the banking system operation were defined.Â